2010
DOI: 10.2478/s11532-009-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of thiourea and its selected derivatives on electroreduction of In(III) in chlorates(VII)

Abstract: It was found that thiourea, N-methylthiourea, N,N'-dimethylthiourea and N-allylthiourea accelerate the electroreduction process of In(III) ions in chlorates(VII). These substances are adsorbed on mercury from chlorates(VII). The relative surface excesses of thiourea and its derivatives increase with the increase of their concentrations and electrode charge. After adding thiourea, N-methylthiourea, N,N'-dimethylthiourea and N-allylthiourea to the solution an acceleration of the electroreduction process of In(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The catalytic effect of metal cation reduction according to the “ cap – pair ” mechanism includes both chemical reactions and heterogeneous charge transfer processes of active complexes on the electrode surface. The surface formation of active complexes within the electrode double layer with the studied metal cations is a plausible mechanism for zinc(II) [ 2 , 3 ], cadmium [ 4 ], indium(III) [ 5 ] and bismuth(III) ion reduction [ 6 , 7 ], while the complexation of europium(III) ions is assumed to proceed in the bulk of the solution as well [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic effect of metal cation reduction according to the “ cap – pair ” mechanism includes both chemical reactions and heterogeneous charge transfer processes of active complexes on the electrode surface. The surface formation of active complexes within the electrode double layer with the studied metal cations is a plausible mechanism for zinc(II) [ 2 , 3 ], cadmium [ 4 ], indium(III) [ 5 ] and bismuth(III) ion reduction [ 6 , 7 ], while the complexation of europium(III) ions is assumed to proceed in the bulk of the solution as well [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the catalytic effect of metal cations electroreduction under "cap-pair" conditions, includes both chemical reactions and heterogeneous processes of charge transfer between the electro-active particle of the complex and the depolarised working electrode. The formation of electroactive complexes with depolarisers is possible both in the adsorption layer for zinc(II) ions [18][19][20], cadmium [21] indu(III) [22,23] and bismuth(III) [24][25][26][27][28][29], and outside the layer for europium(III) ions [30]. The goal of this current paper was to collect and summarise studies on the kinetics and mechanism of action for selected organic substances on the electroreduction of Bi(III) ions in chlorate(VII) solutions in terms of expanding the interpretation of the "cap-pair" effect mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of organic substance effects on the electrode reaction rate is of significant importance in the elaboration of technological or pharmacological characteristics. It was found that the ability of the organic substance, undergoing adsorption on the electrode, to form complexes with the depolarizer in the near-electrode layer and location of the reduction potential of the depolarizer in the area of labile adsorption equilibrium of the organic substance [1][2][3]. A significant effect of activity of water and some polarographically active amino acids on the mechanism and kinetics of Bi(III) ion electroreduction [4,5] was proven which developed the interpretation of the "cap-pair" effect mechanism.…”
Section: Introductionmentioning
confidence: 99%